Risk of high blood pressure in hyperreactive cardiovascular individuals. - Mikhail Benet-Rodríguez (Salud Pública de México, 2018)
Objective. To determine the risk of high blood pressure in cardiovascular hyperreactive individuals identified by the isometric hand-held weight test. Materials and methods. A prospective cohort study was conducted for 5 years, including a total of 419 individuals. Of them, 215 were normoreactive and 204 hyperreactive. The relative risk of hypertension in the hyperreactive individuals and the contribution of cardiovascular hyperreactivity to the development of high blood pressure were determined. The significance level was 0.05. Results. The frequency of new hypertension cases after five years was twice as high in the cohort of hyperreactive subjects compared to the cohort of normoreactive subjects (RR 2.23, 95%CI 1.42, 3.51). The cardiovascular hyperreactivity was the most important variable for predicting of the high blood pressure (OR: 2.73; 95%CI 1.59, 4.54). Conclusions. Cardiovascular hyperreactive individuals have a higher risk of high blood pressure than normorreactive individuals.